ENDS Device Type and Initiation of Combustible Tobacco Products Among Adolescents. Issue 3 (29th June 2020) - Sumbe, Aslesha; Clendennen, Stephanie L; Opara, Samuel C; Jackson, Christian D; Chen, Baojiang; Wilkinson, Anna V; Harrell, Melissa B
Abstract: Introduction: The aim of this study was to determine whether Electronic Nicotine Delivery Systems (ENDS) device type (disposable devices, replaceable cartridges, and refillables) at initial or first ENDS use predicts subsequent initiation of combustible tobacco products (cigarettes, hookah, cigars) among adolescents and/or differentiates between those who initiate use of both ENDS and combustible tobacco products at the same time. Methods: The study examined data from the Texas Adolescent Tobacco and Marketing Surveillance System (TATAMS), a longitudinal population-based cohort of students in major metropolitan areas of Texas ( n = 3907; N = 461 069). Data were collected every 6 months, from 2014 to 2018; 33.9% ( n = 1324; N = 151 784) of the sample initiated ENDS use across this period. Unadjusted and adjusted logistic regression models were used to assess the odds of initiating combustible tobacco products at a subsequent or similar wave as ENDS initiation, given initial ENDS device type. Results: After adjusting for sociodemographic factors, the odds of initiating combustible tobacco use subsequent to ENDS initiation were significantly lower among those who reported using Cartridges as their initial device type compared to those who reported Refillables as their initial device type (adjusted odds ratio = 0.42 [0.18–0.98], p = .05). In addition, after controlling for sociodemographic variables, the odds of initiating combustible tobacco use in the same wave as ENDS initiation were significantly higher among those who reported using Cartridges as their initial device type, compared with those who reported Refillables as their initial device type (adjusted odds ratio = 2.31 [1.05–5.10], p = .04). No significant differences were found in adjusted models when Disposables were compared to Refillables and Cartridges to Disposables. Conclusion: ENDS device type differentiates between adolescents who start using combustible tobacco products at the same time as initial ENDS use, or subsequently. Implications: Previous research has shown ENDS use predicts subsequent combustible use among adolescents, but there is lack of research on the role of specific ENDS device types and the timing of initiation. Findings from this longitudinal study show that initiation of combustible tobacco product use varies by initial ENDS device type among adolescents. These findings can become a focal point for developing interventions for adolescents and could have regulatory implications for ENDS products.